(untitled) (Web of Teachers: Inderscience Research, 2025)
The article presents the development of a practical lesson based on the created methodology for 1st year students of the direction of education "Theory and Practice of Translation (English)", conducted in eight groups at the Tashkent State University of Uzbek Language and Literature named after Alisher Navoi. The purpose of the lesson is to work out and consolidate verbs of motion conjugated by analogy in training exercises, which contributes to a quick understanding and memorization, as well as the active use of these verbs in oral and written speech by students. The article also discusses the etymological connections of Russian words with English words, which we consider as mnemonic devices that contribute to the easy memorization of new lexical units on the basis of associations.